A Study of Consumer Perception on the Use of E-Technology in the Retail Banking Sector: A Comparative Study of Public Sector and Private Sector Banks - Jani, Aashish Shashikant (Indian Journal of Marketing, 2012)
In the new millennium, the growth of the Internet & commerce is changing everyday, so all the banking transactions also need to be performed electronically, i.e. whether it is to pay bills, transfer your funds, to check balance, to get advice or to apply for loans. On the other side, technology is popular because of less cost of operation, increase in banking habits & number of transactions, lack of time with customers, improvement in customer services, etc. However, individual differences, computer literacy, personality and demographic variables reflect the users’ intention to adopt E-banking. Hence, there is a need to fill this gap that though e-technology is provided by the bank, whether it is used effectively by customers? Why some people have not accepted the technology fully, though it provides many advantages to banking customers? This research paper attempts to fill this gap of perceived usefulness & perceived ease of use, by identifying various factors, which will increase the usage of technology among the customers in India.